PENGARUH PENGEMBANGAN SUMBERDAYA MANUSIA DAN DISIPLIN KERJA ERHADAP KINERJA KARYAWAN BPD GAPENSI PROVINSI MALUKU UTARA - Abdullah, Faujia; Jabid, Abdullah W (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2021)
Objective: (1) Does Human Resource Development affect the Employee Performance of Regional Executive Board Indonesian Builders Association of North Maluku Province?; (2) Does Work Discipline affect the Employee Performance of Regional Executive Board Indonesian Builders Association of North Maluku Province? (3) Does Human Resource Development and Work Discipline simultaneously influence the Employee Performance of Regional Executive Board Indonesian Builders Association of North Maluku Province? The number of research samples were 60 employees of Regional Executive Board Indonesian Builders Association of North Maluku Province. Methodology: The test tool used is multiple linear regression analysis using the statistical package for social scientists (SPSS) as a statistical test tool.Finding: Ha1, Ha2, and Ha3 are rejected, at the 5% confidence level.Conclusion: (1) Human Resource Development (HR) had a positive and significant effect on the Employee Performance; (2) Work discipline has a positive and significant effect on the Employee Performance; and (3) Human Resource Development (HR) and work discipline simultaneously have a positive and significant effect on the Employee Performance of Regional Executive Board Indonesian Builders Association of North Maluku Province. This is based on the calculated F value that is greater than the F table value, and the significant value that is smaller than alpha (ÃŽÂ±)